Silane/iodonium salt as redox/thermal/photoinitiating systems in radical and cationic polymerizations for laser write and composites. Issue 4 (12th December 2019) - Wang, Dengxia; Garra, Patxi; Fouassier, Jean Pierre; Lalevée, Jacques
Abstract : Methylphenylsilane (MPS) and octadecylsilane (ODS) are originally proposed here combined with iodonium salt as a highly versatile triple initiating system for redox, photo and thermal polymerizations (both radical and cationic). Abstract : Initiating systems that can be applied to both free radical polymerization (FRP) and cationic polymerization (CP) have attracted much attention due to their unique advantages, such as integrating monomers with completely different structures and properties into a polymerization system to form high-performance and multi-functional (co)polymers. Methylphenylsilane (MPS) and octadecylsilane (ODS) are originally proposed here combined with iodonium salt as a highly versatile triple initiating system for redox, photo and thermal polymerizations (both radical and cationic). In redox polymerization, gel times can be controlled between 1 and 30 min by adjusting the concentrations of silane/iodonium couples or by adding additives ( e.g. stabilizer TEMPOL or different inorganic salts). The combination of silane/Iod with a photoinitiator results in excellent dual photo/thermal initiating ability for both FRP and CP (demonstrated by DSC and RT-FTIR). These newly developed initiating systems can be applied in laser write experiments @405 nm and show excellent spatial resolution performance. Thick carbon or glass fiber/epoxy resin composites are also easily manufactured via a dual approach (first photocuring at the surface and then thermal curing in depth). Importantly, the new initiating systems show excellent storage stability in epoxide resins, which cannot be achieved with classical initiators.